Different clinical manifestations in two siblings with cytomegalovirus infection - L. Álvarez-Hernández (Revista Médica del Hospital General de México, 2017)
In immunocompetent patients, human cytomegalovirus (CMV) infections are generally asymptomatic. Infection by this virus takes on particular importance during pregnancy owing to a risk of congenital infection occurring as a result of fetal transmission. In this article, we report the case of two siblings with this infection. The younger sibling had cystic microphthalmia, which was believed to be secondary to prenatal CMV infection. Given her status as an infectious carrier, she infected her older brother, who had signs and symptoms similar to those of infectious mononucleosis. CMV infection has a wide clinical spectrum, and prenatal CMV infection must be considered in patients within the differential diagnosis of eye malformations.